Group versus individual sessions delivered by a physiotherapist for female urinary incontinence: an interview study with women attending group sessions nested within a randomised controlled trial - Griffiths, F; Pepper, J; Jørstad-Stein, E; Smith, J; Hill, L; Lamb, S (BioMed Central, 2009)
Background: The aim was to explore the concerns and expectations of women invited to attend group physiotherapy sessions for the management of female urinary incontinence and whether the experience changed their views; and to gather recommendations from women attending group sessions on the design and delivery of these sessions. Methods: An interview study nested within a randomised controlled trial in five British NHS physiotherapy departments, including 22 women who had expressed a preference for an individual physiotherapy session but were randomised to, and attended, group sessions. Results: Embarrassment was woven throughout women's accounts of experiencing urinary incontinence and seeking health care. Uncertainty about the nature of group sessions was a source of concern. Attending the first session was seen as a big hurdle by many women. However, a sense of relief was common once the session started, with most women describing some benefit from attendance. Recommendations for design and delivery of the sessions from women focused on reducing embarrassment and uncertainty prior to attendance. Conclusion: Taking account of women's embarrassment and providing detailed information about the content of group sessions will enable women to benefit from group physiotherapy sessions for the management of female urinary incontinence. Trial Registration: Trial registration number: ISRCTN 16772662